Biomonitoring in the Anthropocene: Urban estuary environmental DNA tracks marine fish, terrestrial wildlife, and human diet - Mark Y. Stoeckle; Jesse H. Ausubel (PLoS ONE, 2026)
Managing anthropogenic impacts in urban estuaries asks for up-to-date monitoring of marine life. Here we analyze vertebrate eDNA in New York City’s East River, a rocky estuary channel difficult to survey with mechanical gear and subject to wastewater discharge. We collected water samples weekly for one year and applied spike-in metabarcoding to quantify vertebrate eDNA. Replication experiments demonstrated good reproducibility above about 10 eDNA copies/PCR. We propose a fish censusing scale based on absolute eDNA abundance. Local marine fish eDNA followed a classic hollow curve species abundance distribution over four orders of magnitude, with abundant and common taxa comprising about 25% of species and 95% of fish eDNA. There was a 10-fold increase in local marine fish eDNA in summer and seasonal differences among taxa consistent with known phenology. Two fish species were newly abundant in comparison to an eDNA survey at the same site in 2016. Levels of other vertebrate eDNA—domesticated animal, non-fish wildlife, and dietary fish—were correlated with human eDNA levels, consistent with a shared wastewater source. Wastewater eDNA identified the commonest urban mammals, land birds, and household pets. Proportions of dietary animal eDNA in wastewater closely approximated proportions in national consumption statistics, opening a window into human diet assessment. Effort and cost for the weekly shoreline survey were modest. Vertebrate eDNA metabarcoding with spike-in quantification enabled weekly monitoring of urban estuary fish populations, identified overlooked newly abundant species, and reported on terrestrial wildlife and human diet.